UJI EFEKTIVITAS DAN IDENTIFIKASI SENYAWA AKTIF EKSTRAK DAUN SIRSAK SEBAGAI PESTISIDA NABATI TERHADAP MORTALITAS KUTU DAUN PERSIK (Myzus persicae Sulz) PADA TANAMAN CABAI MERAH (Capsipcum annum L.) - Dwi Desiyanti, Ni Made; Dira Swantara, I Made; Sudiarta, I Putu (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016DO - 10.24843/JCHEM.2016.v10.i01.p01, 2016)
The study of isolation and identification of the active compounds of soursop ( Annona muricata L.) leave extract were conducted . The metabolite extraction was conducted using maceration method with 96 % ethanol. The ethanol extract was used to test the mortility of aphid ( Myzus persicae S.), with LC 50 of 100 ppm. The n-hexane, chloroform, and n-buthanol were used to fractionate the ethanol extract. The mortality test of those three extracts showed the LC 50 of 545.12 ppm, 136.26 ppm and 117.73 ppm, respectively. The n-butanol extract was separated using silica gel column chromatography with chloroform: ethanol: water (5:4:1), as the mobile phase. The fractions resulted were FI, FII, FIII, FIV and FV. The mortality test indicated that FII was the best with LC 50 of 596.48 ppm. The FII was purified using silica gel column chromatography, resulting three fractions (FII.1, FII.2 and FII.3).  The mortality test of those fractions indicated that FII.2 showed the best result with LC 50 of 601.17 ppm. The UV-Vis and IR spectra showed that FII.2 fraction contained flavonoides under the flavonon family.
Keywords: soursop (Annona muricata L.), aphid (Myzus persicae S.) and flavonoids